Meta‐analysis of associations between empathy and alcohol use and problems in clinical and non‐clinical samples. (29th May 2022) - Kumar, Lakshmi; Skrzynski, Carillon J.; Creswell, Kasey G.
Abstract: Aims: To (1) measure the aggregated effect size of empathy deficits in individuals with alcohol use disorder (AUD) compared with healthy controls, (2) measure the aggregated effect sizes for associations between lower empathy and heavier alcohol consumption and more alcohol problems in non‐clinical samples and (3) identify potential moderators on the variability of effect sizes across studies in these meta‐analyses. Method: PsycINFO, PubMed and Google Scholar were searched following a pre‐registered International Prospective Register of Systematic Reviews (PROSPERO) protocol (CRD42021225392) and Preferred Reporting Items for Systematic Reviews and Meta‐Analyses (PRISMA) methodology. We meta‐analyzed (using random‐effects models) mean differences in empathy between individuals with AUD compared with healthy controls and associations between empathy and alcohol consumption and alcohol problems in non‐clinical samples. A total of 714 participants were included in the meta‐analysis on clinical samples; 3955 were included in the meta‐analyses on non‐clinical samples. Results: Individuals with AUD reported significantly lower empathy than healthy controls [Hedges' g = −0.53, 95% confidence interval (CI) = −0.91, –0.16, k = 9, P < 0.01, Q = 40.09, I 2 = 80.04]. Study quality [ Q = 1.88, degrees of freedom (d.f.) = 1, P = 0.17] and gender ( β = −0.006, Z = −0.60, P = 0.55) were not moderators. Increases in age corresponded to an increase in effect size ( β = 0.095, Z = 3.34, P < 0.001). Individuals with AUD (versus healthy controls) had significantly lower cognitive (Hedges' g = −0.44, CI = −0.79, –0.10, P < 0.05), but not affective empathy (Hedges' g = −0.19, CI = −0.51, 0.14, P = 0.27), and the difference between these was significant ( Z = 2.34, k = 6, P < 0.01). In non‐clinical samples, individuals with lower (versus higher) empathy reported heavier alcohol consumption ( r = −0.12, CI = −0.15, –0.09, k = 11, P < 0.001, Q = 9.68, I 2 = 0.00) and more alcohol problems ( r = −0.08, CI = −0.14, –0.01, k = 7, P = 0.021, Q = 6.55, I 2 = 8.34). There was no significant heterogeneity across studies. Conclusion: Individuals with alcohol use disorder appear to show deficits in empathy compared with healthy controls. Deficits are particularly pronounced for older individuals and for cognitive (versus affective) empathy. In non‐clinical samples, lower empathy appears to be associated with heavier alcohol consumption and more alcohol problems.